Dual solutions for the oblique stagnation-point flow of hybrid nanofluid towards a shrinking surface: effects of suction - Yahaya, Rusya Iryanti; Md Arifin, Norihan; Pop, Ioan; Md Ali, Fadzilah; Mohamed Isa, Siti Suzilliana Putri (Elsevier, 2023)
The suction draws the ambient fluid towards the permeable surface. Generally, suction delays the detachment of a boundary layer from a surface and improves the heat transfer rate. The current study analyses the effects of suction on the oblique stagnation-point flow of hybrid nanofluid (i.e., Cu-Al2O3/H2O) over a shrinking surface. Similarity transformations are adopted to reduce the governing equations and boundary conditions into non-linear differential equations and boundary conditions. Then, numerical computation is carried out using the bvp4c package. Dual solutions are found, and the first solution is identified as the stable solution through a stability analysis. The increase in the suction parameter enhances the normal and shear components of the skin friction and the temperature gradient. Consequently, it reduces the momentum and thermal boundary layer thickness to slow down boundary layer separation and enhances the heat transfer rate at the shrinking surface.